Pengaruh Literasi Keuangan, Gaya Hidup, Dan Financial Distress Terhadap Perilaku Keuangan Mahasiswa Akuntansi UPN Veteran Jawa Timur - Reza Afrizal Rachman; Indrawati Yuhertiana; Acynthia Ayu Wilasittha (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the influence of financial literacy, lifestyle and financial distress on the financial behavior of Accounting students at UPN Veteran East Java. The type of data used in this research uses primary data originating from respondents' answers obtained from questionnaires distributed to all Accounting students at UPN Veteran East Java totaling 93 respondents with a sampling technique using a simple random sampling formula. This research uses a quantitative type of research with PLS as the test tool. Research findings show that financial literacy, lifestyle and financial distress contribute to the financial behavior of Accounting students at UPN Veteran East Java.